The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9cp01532a
|View full text |Cite
|
Sign up to set email alerts
|

On the interaction of hyaluronic acid with synovial fluid lipid membranes

Abstract: All-atom molecular dynamics simulations have been used to investigate the adsorption of low molecular weight hyaluronic acid to lipid membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 62 publications
1
50
0
Order By: Relevance
“…There was no significant difference between force profiles measured across the POPC dispersion and across HA–POPC mixture (0.5 mg/mL: 0.3 mM, Figure 5 b—red symbols) once HA was introduced. We may conclude the HA–POPC complex [ 34 , 56 ] was not trapped between the surface, but rather that it was squeezed out between POPC bilayers as the surfaces approached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference between force profiles measured across the POPC dispersion and across HA–POPC mixture (0.5 mg/mL: 0.3 mM, Figure 5 b—red symbols) once HA was introduced. We may conclude the HA–POPC complex [ 34 , 56 ] was not trapped between the surface, but rather that it was squeezed out between POPC bilayers as the surfaces approached.…”
Section: Resultsmentioning
confidence: 99%
“…In the hydration lubrication paradigm surfaces interact via fluid but tenaciously attached hydration layers exposed by their boundary layers at the slip plane, resulting in low friction as surfaces slide past each other [ 12 , 58 ]. Previous studies [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 56 , 59 , 60 , 61 , 62 , 63 , 64 ] showed that HA interacts with PC lipids when they are dispersed in aqueous solution or when the phospholipids are incubated with pre-adsorbed HA on a surface, due to charge-dipole interactions between the negatively charged HA and the exposed zwitterionic phosphocholine headgroups. Thus one would expect that HA would adsorb at a phospholipid-bilayer/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…From the resulting set of 6114 residue pairs, we carried out further renements to identify a subset for which HBs were most likely to be present. A wide range of HB distance (2.2-4.0 A) and angle criteria (90-180 ) have been proposed [87][88][89] in the literature. Because consensus about HB distances and angles is not established, and the optimal HB distance or angle is strongly species dependent, we developed a quantummechanically derived approach to selecting distance and angle cutoffs.…”
Section: Curation Approachmentioning
confidence: 99%
“…Block averaging was used to compute both the mean and standard deviation over the sampled trajectories. Dihedral angle and hydrogen bonding analyses were performed using the MDAnalysis package [89,90]. pKa analysis was performed using the DelPhiPKa webserver [91,92].…”
Section: Analysesmentioning
confidence: 99%